Pengaruh Model Pembelajaran Berbasis Masalah Berbasis TPACK dalam Meningkatkan Berpikir Kritis Siswa pada Pembelajaran Pendidikan Pancasila - Putri, Fannia Sulistiani; Dewi, Dinie Anggraeni; Furnamasari, Yayang Furi (Indo-MathEdu Intellectuals Journal, 2024)
Pancasila education plays a crucial role in shaping national character and identity from an early age. However, teaching complex concepts in Pancasila Education to elementary school students, especially at the fourth grade level, can be a challenge in itself. Apart from that, developing critical thinking skills at this age is also important, considering the importance of these abilities in understanding and applying national values. This research aims to determine the effect of using the Problem Based Learning (PBL) model which is based on the TPACK (Technological Pedagogical Content Knowledge) concept in improving students' critical thinking skills in learning Pancasila Education in class IV elementary school. How the research was carried out at SDN Pagarsih. The experimental method used involved two groups of students: a control group that took part in conventional learning and a treatment group that applied the TPACK-based PBL model. The approach in this research is quantitative with a quasi-experimental type and nonequivalent pre-test and post-test control group design. The results of data analysis showed that students involved in the TPACK-based PBL Model showed significant improvements in their critical thinking abilities compared to the control group. Thus, it can be concluded that the use of the TPACk-based PBL model in learning can influence students' critical thinking abilities, especially in learning Pancasila education